When central banks buy corporate bonds: Target selection and impact of the European Corporate Sector Purchase Program - Galema, Rients; Lugo, Stefano (Journal of Financial Stability, 2021)
We study the timing of the European Corporate Sector Purchase Program and its direct effect on corporate financing decisions. Consistent with the goal of reducing credit premia, more timely purchases are observed for eligible bonds characterized by higher credit risk. Firms effectively targeted increase their relative use of market debt and the maturity of newly issued bonds more than eligible but not (yet) targeted issuers. The estimated effect is not driven by the verified relation between selection and credit risk. The program has fostered the ability to tap credit markets directly especially for eligible corporations whose bonds are actually purchased.